IMPROVING STUDENTS' LITERACY SKILLS THROUGH THE DEVELOPMENT OF A PROBLEM-BASED LEARNING MODEL BASED ON HOTS - Danis, Amir; Julia, Nur Tri; Maulida, Zulfi; Nabila, Nabila (Jurnal Buah Hati, 2025)
The low achievement of Indonesian students in the Programme for International Student Assessment (PISA) highlights the need for innovative learning models that not only emphasize cognitive aspects but also foster students’ character development. This study aims to develop a Problem Based Learning (PBL) model integrated with Higher Order Thinking Skills (HOTS) and character education to improve the literacy skills of elementary school students. The research employed a Research and Development (R&D) approach using the ADDIE development model, which consists of analysis, design, development, implementation, and evaluation stages. The study involved 28 fourth-grade students. The research instruments included validation sheets, observation sheets, student and teacher response questionnaires, and literacy tests covering reading, numeracy, science, and digital literacy. The results indicate that the learning model was considered highly valid with an average validation score of 88.5%. The implementation of the PBL-HOTS-Character model significantly improved students’ literacy skills with an average score of 87.5, consisting of reading literacy (88), numeracy (85), science literacy (87), and digital literacy (90). Students’ character education also improved with an average score of 73.4. The two-way ANOVA analysis revealed that the learning model, character education, and their interaction had a significant effect on students’ literacy, with a determination coefficient of 66.1%. In conclusion, the PBL model integrated with HOTS and character education is effective in enhancing literacy skills while strengthening students’ character. This model is highly relevant to support the implementation of the Merdeka Curriculum and the realization of the Pancasila Student Profile.